Designing speech for a recipient : the roles of partner modeling, alignment and feedback in so-called 'simplified registers'/ Kerstin Fischer. - Fischer, Kerstin, 1966- (Pragmatics & beyond ;, 2016)
This study asks how speakers adjust their speech to their addressees, focusing on the potential roles of cognitive representations such as partner models, automatic processes such as interactive alignment, and social processes such as interactional negotiation. The nature of addressee orientation is investigated on three candidates for so-called 'simplified registers': speech to children (also called 'motherese' or 'baby talk'), speech to foreigners (also called 'foreigner talk') and speech to robots. The volume integrates research from various disciplines, such as psychology, sociolinguistics, psycholinguistics and conversation analysis, and offers both overviews of child-directed, foreigner-directed and robot-directed speech and in-depth analyses of the processes involved in adjusting to a communication partner.